2017
DOI: 10.6018/turismo.40.310101
|View full text |Cite
|
Sign up to set email alerts
|

Patrimonio, viñedo y turismo: recursos específicos para la innovación y el desarrollo territorial de Castilla-La Mancha

Abstract: RESUMENLa revalorización del patrimonio cultural y la promoción del enoturismo constituyen factores indiscutibles de desarrollo en Castilla-La Mancha, puesto que, una vez integrados, desempeñan un papel clave en la consolidación de los procesos de gobernanza y en la creciente diversificación económica de las explotaciones agrarias. La implantación de estas estrategias está resultando bastante interesante en ciudades de tamaño medio como Alcázar de San Juan, ejemplo que permite descubrir la importancia de la co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 5 publications
0
9
0
5
Order By: Relevance
“…In essence, wine as a cultural product has emerged as the key factor for tourism development in Gaia through the interrelation of changing demands for cultural tourism and the wineries' promotional and economic diversification strategies [11,36,92]. In line with literature, it can therefore be concluded that the culture and use of wine based on wine tourism experiences bears a clear connection with territorial sustainability [64].…”
Section: Discussionmentioning
confidence: 97%
“…In essence, wine as a cultural product has emerged as the key factor for tourism development in Gaia through the interrelation of changing demands for cultural tourism and the wineries' promotional and economic diversification strategies [11,36,92]. In line with literature, it can therefore be concluded that the culture and use of wine based on wine tourism experiences bears a clear connection with territorial sustainability [64].…”
Section: Discussionmentioning
confidence: 97%
“…These are both emblematic aspects of the LEADER programme. On these lines, various articles have examined the impact of LEADER on for example ways of combining traditional agricultural and livestock practices with agritourism [18,19] wine tourism [20,21], olive oil tourism [22], dehesa grasslands [23], landscapes [24], local skills, knowledge and festivals [25] or the impact on the structure of the rural tourism sector produced by LEADER-related actions, which resulted in an excess supply of accommodation, which was often of poor quality [26]. Other research has focused on the role of LEADER in halting the depopulation of rural areas [27][28][29], strengthening their level of resilience [30] or simply, as a new methodology for intervention in the development of rural areas [31,32], known as the LEADER approach [33,34].…”
Section: Introduction: State Of the Artmentioning
confidence: 99%
“…El enoturismo comprende los distintos elementos que configuraban el patrimonio vitivinícola, agrupándolos en un patrimonio material o tangible, los inmateriales o intangibles y el patrimonio natural y genético (Plaza, Cañizares & Ruiz, 2017). En las páginas webs de estos Monasterios se fomentan las actividades enoturísticas, mencionando la elaboración del vino, pero sólo 3 monasterios tienen actividades específicas relacionadas con el enoturismo como visitas a la bodega, catas de vino o similares, los dos italianos y el alemán, estas actividades se basan en propuestas clásicas de enoturismo, como degustación de vino y los recorridos en los viñedos y las instalaciones.…”
Section: Canales De Promoción Internos Y Externos De Los Monasterios ...unclassified